Improving the NO2 Gas Sensing Performances at Room Temperature Based on TiO2 NTs/rGO Heterojunction Nanocomposites - Yan Ling; Yunjiang Yu; Canxin Tian; Changwei Zou (Nanomaterials, 2024)
The development of energy-efficient, sensitive, and reliable gas sensors for monitoring NO2 concentrations has garnered considerable attention in recent years. In this manuscript, TiO2 nanotube arrays/reduced graphene oxide nanocomposites with varying rGO contents (TiO2 NTs/rGO) were synthesized via a two-step method for room temperature NO2 gas detection. From SEM and TEM images, it is evident that the rGO sheets not only partially surround the TiO2 nanotubes but also establish interconnection bridges between adjacent nanotubes, which is anticipated to enhance electron–hole separation by facilitating electron transfer. The optimized TiO2 NTs/rGO sensor demonstrated a sensitive response of 19.1 to 1 ppm of NO2, a 5.26-fold improvement over the undoped TiO2 sensor. Additionally, rGO doping significantly enhanced the sensor’s response/recovery times, reducing them from 24 s/42 s to 18 s/33 s with just 1 wt.% rGO. These enhancements are attributed to the increased specific surface area, higher concentration of chemisorbed oxygen species, and the formation of p-n heterojunctions between TiO2 and rGO within the nanocomposites. This study provides valuable insights for the development of TiO2/graphene-based gas sensors for detecting oxidizing gases at room temperature.